KONSUMSI MINUMAN RICH SUGAR TEA DAN LESS SUGAR TEA TERHADAP PERUBAHAN PH SALIVA - Benni Benyamin; Ani Subekti; Sulur Joyo Sukendro (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2017)
TITLEEffect of rich and less sugar tea consumptions to pH salivaABSTRACTEveryday people often consume sweetened tea drinks. The sugar content mixed into the tea drink varies greatly depending on the tastes of the people. Sugar is a simple carbohydrate that can affect salivary acidity (pH). This study aims to determine differences in salivary pH after consuming tea drinks with different levels of sugar different.This research type is Experiment. Research design is pre test and post test with control group. The number of samples is 45 people of Dukuh Temuireng village Sukorejo Regency Pemalang with age 20-35 years. Sampling method using random sampling technique. There are 2 groups of treatment, the group consumes rich sugar tea and less sugar tea. The control group was the group that consumed free sugar tea. Analysis of data in use is One Way Anova Test.The results showed that salivary pH after drinking rich sugar tea decreased the pH 7 value by 80%. And the less sugar tea group decreased the pH 7 by 73%. While the salivary pH after drinking free sugar tea increased at pH value 53%. One Way Anova test results are sig. 0.00 0.05 which means there is a difference of salivary pH in the 3 groups of different sugar levels. Sugar levels in tea drinks can affect the saliva pH of a person who consumes tea drinks. The fluoride content in tea can prevent the occurrence of dental caries but if drinking tea with excessive sugar will result in the occurrence of caries in the teeth. Keywords : Rich sugar tea, less sugar tea , pH of saliva